2009
DOI: 10.2165/11316560-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The Causes of and Factors Associated with Prescribing Errors in Hospital Inpatients

Abstract: Prescribing errors are common, they result in adverse events and harm to patients and it is unclear how best to prevent them because recommendations are more often based on surmized rather than empirically collected data. The aim of this systematic review was to identify all informative published evidence concerning the causes of and factors associated with prescribing errors in specialist and non-specialist hospitals, collate it, analyse it qualitatively and synthesize conclusions from it. Seven electronic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
155
2
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 51 publications
6
155
2
8
Order By: Relevance
“…Moreover, prudent antibiotic prescribing and pharmacovigilance should be given more attention as many studies reported that students felt that there was a lack of training in these two subjects. However, as prescribing errors are caused by multiple factors, changing undergraduate CPT education is only part of the solution, and multifaceted interventions in clinical practice are needed that address the different aspects of the prescribing process 97.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prudent antibiotic prescribing and pharmacovigilance should be given more attention as many studies reported that students felt that there was a lack of training in these two subjects. However, as prescribing errors are caused by multiple factors, changing undergraduate CPT education is only part of the solution, and multifaceted interventions in clinical practice are needed that address the different aspects of the prescribing process 97.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, medications can be associated with false positive results on toxicology testing (Brahm et al 2010;Rengarajan and Mullins 2013) or modify other laboratory findings leading to an incorrect diagnosis. Lack of information or confusion about prescribed medications and dosages can also contribute to medical errors (Fitzgerald 2009;Procyshyn et al 2010;Tully et al 2009). …”
Section: Rationalementioning
confidence: 99%
“…3,4 Therefore, after the first day, it was decided that pharmacy staff, like other staff in the clinic, would take mandatory breaks during their shifts. No food or drink was allowed in the clinic, and staff wore scrubs, gloves, masks, and face shields while working.…”
Section: Staffing and Workloadmentioning
confidence: 99%